Hayward Annual '78. - Ciobotaru, Gillian Wise; Derges, Susan; Drew, Joanna; Kent, Sarah; Lippard, Lucy R.; Pope, Terry (London : Hayward Gallery, 1978)
Taylor, Wendy ; Blow, Sandra ; Petherbridge, Deanna ; Morris, Adrian ; Lijn, Liliane ; Maler, Leopoldo ; Jaray, Tess ; Burns, Pamela ; Hunter, Alexis ; Cox, Stephen ; Hiller, Susan ; Sandle, Michael ; Farrer, Julia ; Leapman, Edwina ; Kelly, Mary ; Furlonger, Steve ; Chaimowicz, Marc Camille ; Beere, Sue ; Donagh, Rita ; Ciobotaru, Gillian Wise ; Pope, Terry ; Derges, Susan ; Frink, Elisabeth
biografie, bibliografie
Hayward Annual '78, Hayward Gallery, London, 23 August - 8 October 1978
Engels
boek